2017
DOI: 10.1590/0102.3772e3336
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da Vergonha em Adolescentes: ‘The Other as Shamer Scale’

Abstract: RESUMO A vergonha, entendida como uma emoção autoconsciente, multifacetada e socialmente focada, desempenha um papel central na saúde mental dos indivíduos. Nos adolescentes, é também uma experiência frequente, sendo importante a sua avaliação para a investigação e prática clinica. Este estudo pretende validar uma medida breve de vergonha externa (Escala de Vergonha Externa - Versão breve para Adolescentes [OASB-A]). Participaram 834 adolescentes com uma média de 15 anos. O modelo final da OASB-A (8 itens), ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The reliability coefficient of OAS-2 in its original study was found to be .82. In addition, the OAS-2's internal consistency was .89 for Italian university students (Saggino et al, 2017), .92 for Portuguese adolescents (Cunha et al, 2017), and .85 for children (Benevides et al, 2016). The reliability coefficients in this research are similar (.88,.89,and .89,Study 1,2,and 3,respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reliability coefficient of OAS-2 in its original study was found to be .82. In addition, the OAS-2's internal consistency was .89 for Italian university students (Saggino et al, 2017), .92 for Portuguese adolescents (Cunha et al, 2017), and .85 for children (Benevides et al, 2016). The reliability coefficients in this research are similar (.88,.89,and .89,Study 1,2,and 3,respectively).…”
Section: Discussionmentioning
confidence: 99%
“…CR in this study is sufficient, with .88. Temporal reliability was also studied for Portuguese adolescents (.73;Cunha et al, 2017) and Portuguese children (.55;Benevides et al, 2016). In this present research temporal reliability was found to be .86.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Other as Shamer Scale for Adolescentsbrief version (OAS-B-A, Cunha et al, 2016) is an adaptation for adolescents of OAS-2 for adults (Matos et al, 2015), which in turn is a short version of the original adult scale (Other as Shamer Scale -OAS, Goss et al, 1994). It aims to assess external shame, how adolescents think about the way others see them, through 8 items.…”
Section: Depression In Institutionalized Adolescentsmentioning
confidence: 99%
“…The other as shamer for adolescents-short form (OAS-SF). The Portuguese version was used (Cunha, Xavier, Cherpe, & Gouveia, 2017;Goss, Gilbert, & Allan, 1994). This self-report measure consists of eight items designed to measure external shame (i.e., what the subjects think about the way others see them).…”
Section: Dass-21mentioning
confidence: 99%